ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL BELAJAR ANAK TUNAGRAHITA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SLB WARAQIL JANNAH KEC. X KOTO PANINJAUAN SUMATERA BARAT - Yarmeli Yarmeli; Nyayu Khodijah; Muhammad Fauzi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
This study aims to find out and analyze what factors influence the learning outcomes of children with intellectual disabilities and dual mental retardation in Islamic religious education subjects at SLB Waraqil Jannah Kec. X Koto Pan Overview West Sumatra. The study only focused on three factors, the first is the type of disability, intelligence level and learning motivation factors. This research is a quantitative research. The sample in this study amounted to 29 mentally retarded children and multiple mentally retarded children. Data collection methods used were questionnaire and documentation methods which were then analyzed using the Chi Squaer formula. The results of the study showed that there was no influence of the three research variables with the acquisition of a disability value of 1.19225, the price of Kai Squared was much smaller on the significance table of 5% or 1% or 40.113 <1.19255 <46.963. The acquisition value of the intelligence level of 5.4452558 which is relatively low than the price of Kai Square is much smaller in the significance table of 5% or 1% or 40.113 <5.4452558 <46.963. The value of learning motivation of 0.117347379 which is relatively low than the price of Kai Squared is much smaller in the significance table of 5% or 1% or 41,337 <0,117347379 <48,278.